Deepening the Spiritual Meaning in Ibn Kathir's Tafsir of Surah Fussilat Verses 30-32 - Alif Subbanul Qirom; Uus Husni Hoer; Moh Asror; Danis Tsaltsa Syahidah (Values: Jurnal Kajian Islam Multidisiplin, 2026)
This research explores the spiritual meaning contained in the interpretation of Surah Fussilat verses 30–32 according to Ibn Kathir. Using a qualitative method through library research, this study examines the theological messages within the verses, including steadfast faith (istiqamah), the descent of angels, and the promise of paradise for believers. Ibn Kathir, using the tafsir bil-ma’tsur approach, explains these verses by referring to Qur’anic evidence, prophetic traditions, and narrations from the companions. His interpretation emphasizes that istiqamah is not only a statement of faith but also a consistent commitment to monotheism and obedience to Allah. The descent of angels is interpreted as a form of divine reassurance, providing calmness and eliminating fear at significant moments in a believer’s life. The verses further describe the reward of eternal paradise as a manifestation of Allah’s mercy for those who remain steadfast. The findings show that Ibn Kathir’s interpretation of Surah Fussilat 30–32 presents profound spiritual lessons that remain relevant for contemporary Muslim life, particularly in strengthening inner peace, resilience, and spiritual consciousness.